Simulation on a Novel Solar High-temperature Thermochemical Coupled Phase-change Reactor. (May 2015) - Ma, T.T.; Zhu, Y.Z.; Chen, H.J.; Ma, Y.; Yang, L.
Abstract: Solar high-temperature thermochemical process is a promising concept to produce hydrogen as well as basic chemical materials by concentrated solar energy. An important feature of this technology is the design of a satisfactory reactor. A novel solar high-temperature thermochemical coupled phase-change reactor based on a special-shaped high-temperature heat pipe (SHHP) receiver is presented. The SHHP integrated with phase-change heat transfer, temperature leveling of heat pipe and heat plate (flat plate heat pipe) separates the upper reaction chamber and the lower solar absorber. In this manner, radial temperature gradient in absorber and axial temperature gradient in reaction chamber will be lowered, thus to enhance safety and thermochemical conversion efficiency of the solar reactor. A three-dimensional model of the reaction chamber coupling heat transfer with nitrogen as working fluid instead of reactants is developed to optimize geometry configurations. The temperature distribution of the reactor wall and the working gas are presented. The impact of the inlet/outlet configurations and arrangement of heat pipes in heat plate are investigated. The results show that different inlet/outlet positions has significant influence on the thermo-fluid behavior, and the existence of the heat pipes on heat plate enhances the heat transfer in reaction chamber.